Capital structure and financial performance of listed non-financial firms in Ghana - Ankomah, Kwadwo; Samena, Frederick Akpali; Sikayena, Isaiah; Ofori-Oppong, Patrick; Arpoh-Baah, Bernard; Boadi, Emmanuel; Harley, Karen Awo (Asian Journal of Empirical Research, 2023)
Capital structure and its impact on firm performance is a key issue in finance, and there are a number of theories and empirical papers that explain this relationship. Using secondary data from listed companies that have traded on the Ghana Stock Exchange (GSE) from 2016 to 2020, the study specifically examines the effect of short-term debt, long-term debt, and total debts on the operational efficiency of listed non-financial companies in Ghana. The study shows that a firm's return on assets decreases as its amount of debt accumulation rises. Also, some firm-specific variables have small but significant impacts on enterprises' profitability. The study recommends that, to ensure that there is adequate cash available for the company's ongoing operations, corporate finance managers should ensure working capital is managed properly and responsibly. Also, in the extreme case where a short-term borrower facility is unavoidably required and must be acquired, the study advises administrators to make sure that the total amount of short-term obligations taken on as a percentage of the capital structure is less than the sum of non-current liabilities and equity in total assets.